Efficacy of Lumax EZ, Atrazine, Acuron, Armezon, Sharpen, Outlook, Verdict, and Prowl H2O in Irrigated Glyphosate-Resistant Corn - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2015)
All treatments provided statistically superior control of Palmer amaranth compared to the control or a single application of glyphosate. All treatments provided excellent control of all other weed species. Although all herbicide tank mixes elevated corn yield compared to the control, there were no statistically significant differences among herbicides in their ability to do so.
Keywords: weed science; weed control; irrigated glyphosate-resistant corn; tank mixes; herbicide; Lumax EZ; atrazine; Acuron; Armezon; Sharpen; Outlook; Verdict; Prowl H2O; Palmer amaranth